Practical application of systemizing expedition research results in the form of taxonomy - Yevhenii Shapovalov; Viktor Shapovalov; Roman Tarasenko; Zhanna Bilyk; Irina Shapovalova; Adrian Paschke; Fabian Andruszkiewicz (Academy of Cognitive and Natural Sciences, 2022)
Data processing is complicated nowadays due to its vast amount and low structuration level. Perspective field to provide such structuration is exceptional studies because, in most cases, they foresee measuring parameters planned before such expeditions. Therefore, it is possible to define the parameters that will be measured and prepare forms to fill them during the expedition. This study substantiates the way of processing such data in the form of ontologies, providing structuring and interoperability of expedition data by providing a similar structuring approach. The case of using such an approach based on real-life expedition study in the field of the environment of the National Center "Junior Academy of Sciences of Ukraine" is described. The approach foresees using Excel to define the parameters that will be measured during an expedition in the form of table's columns. Each row in such a table will represent the place or name of the research object. An additional column is devoted to inserting geolocation. After providing the research, such files are uploaded into Polyhedron system and ontology is generated. Such ontologies are stored and integrated into ArcGis and can be used to present their own results and provide background research by other researchers.